Problematika Wanita Karir dalam Membangun Keluarga Sakinah di Desa Sumber Salak Kecamatan Ledokombo Kabupaten Jember - Sholehah, Luluk Alfiatus; Rohmawati, Silfiyah (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2023)
A career woman inevitably faces challenges in establishing a harmonious family within the family sphere and in a workplace environment that may not be supportive. Generally, the issues often encountered by career women include a need for more time spent with the family, diminished communication within the family, and suboptimal performance in their work. From this phenomenon, this research aims to describe the problems faced by career women in building a harmonious family and understand how career women build a harmonious family in the Dusun Salak of Sumber Salak, Ledokombo, Jember. The qualitative research method uses a case study approach or direct field immersion. The findings of this research indicate that: 1) The problems faced by career women in building a harmonious family include minimal interaction with the family, a lack of quality time spent together, and inadequacies in child-rearing. 2) How career women build a harmonious family in the Dusun Salak of Sumber Salak, Ledokombo, Jember involves fulfilling their duties and roles based on the Quran and Hadith, fostering mutual respect and affection among family members, maintaining trust, and nurturing good relationships with parents and in-laws.